AN INSIGHT TO RETINITIS PIGMENTOSA AND MANAGEMENT BY AYURVEDIC THERAPIES - V T, Renu; K V, Mamatha; V, Hamsaveni; Mishra, Baidyanath (International Journal of Ayurveda and Pharma Research, 2015)
Retinitis pigmentosa (RP) is a hereditary group of degenerative eye diseases caused by genetic mutations affecting retina that lead to severe vision loss and blindness. In Ayurveda, the conditions like Kapha vidagdha drushti, Hraswajadya and Dhoomadarshi which has night blindness as the cardinal feature can be simulated to different stages of RP. Certain authenticated therapies are explained in our ancient literature which are time tested such as Tarpana (Nourishing eye bath therapy), Putapaka (eye bath therapy), Anjana (Collyrium), Nasya (Processed liquid instillation through nostrils by drops or powders), Sirodhara (application of continuous stream of oil over the head), Vasti (Medicated enema) etc. through which considerable results are achieved. The drugs and procedures described in Ayurveda have probable mode of action in crossing the blood retinal barrier, a protective measure of cells surrounding the retina. The extent of benefit in alleviating the clinical features of RP happens possibly because of the phytonutrients present in the formulations applied through various procedures crossing the blood retinal barrier. To validate the management protocol explained in classics, a retrospective study was conducted on five patients selected from the OPD/IPD of Dept of Shalakya Tantra of Sri Kalabyraveshwaraswamy Ayurvedic Medical College, Hospital & Research centre, Vijayanagar (SKAMCH & RC). The results assessed statistically proved significant in certain parameters indicating a beneficial effect in reducing the subjective symptoms of Retinitis pigmentosa.